2018
DOI: 10.1158/1538-7445.am2018-3792
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3792: Intratumoral CD56bright natural killer cells are associated with improved survival in bladder cancer

Abstract: Antitumor immune responses are largely mediated by cytotoxic lymphocytes (CD8+ T cells) that recognize tumor-associated antigens presented in the context of a major histocompatibility complex class I molecule (MHC I). However, many tumors downregulate MHC I expression as a means of immune escape. Under these conditions, additional effector lymphocytes, such as natural killer cells (NK cells) which mediate non-MHC restricted cytotoxicity, provide antitumor defenses. Although the presence of intratumoral CD8+ T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Surprisingly, a more recent flow cytometric analysis of fresh tissue from patients with both NMIBC and muscle invasive bladder cancer (MIBC) has suggested that improved survival may be linked to the presence of CD56 bright NK cells within the tumor which are found in much smaller numbers than their CD56 dim counterparts. These cells are functionally active compared to the reduced cytokine secreting capacities of the CD56 dim subset (64). This might explain the findings of the previous study which did not distinguish between the subsets in their analysis.…”
Section: Natural Killer Cell Subsets and γδ T Cellsmentioning
confidence: 99%
“…Surprisingly, a more recent flow cytometric analysis of fresh tissue from patients with both NMIBC and muscle invasive bladder cancer (MIBC) has suggested that improved survival may be linked to the presence of CD56 bright NK cells within the tumor which are found in much smaller numbers than their CD56 dim counterparts. These cells are functionally active compared to the reduced cytokine secreting capacities of the CD56 dim subset (64). This might explain the findings of the previous study which did not distinguish between the subsets in their analysis.…”
Section: Natural Killer Cell Subsets and γδ T Cellsmentioning
confidence: 99%